Flow transition design in hydraulic structures - Mazumder, S. K. (New York, NY: CRC Press, 2020)
Transitions are provided in hydraulic structures for economy and efficiency. This book covers all types of flow transitions: sub-critical to sub-critical, sub-critical to super critical, super-critical to sub-critical with hydraulic jump, and super-critical to super-critical transitions. It begins with an introduction followed by characteristics of flow in different types of transitions and procedures for hydraulic design of transitions in different structures. Different types of appurtenances used to control flow separation and ensure uniform flow at exit of transition and diffusers are included. Examples of hydraulic design of a few typical hydraulic structures are given as well.
OCLC-licensed vendor bibliographic record.
Keywords: Hydraulic structures -- Design and construction; Transition flow; SCIENCE / Environmental Science; TECHNOLOGY / Engineering / Civil